2004
DOI: 10.1007/s00192-004-1154-8
|View full text |Cite
|
Sign up to set email alerts
|

Is the leak point pressure alone an accurate indicator of intrinsic sphincteric deficiency?

Abstract: The aim of this study was to determine the characteristics of women who meet the criteria for intrinsic sphincteric deficiency (ISD) on maximum urethral closure pressure (MUCP) but not on leak point pressure (LPP) measurement. We performed a cross-sectional chart review of every patient who underwent multichannel, microtransducer urodynamic testing in our center between 1994 and 1996 (n=423). From this population we culled a sub-population of women who fit into one of the following two groups: women with no ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Despite this, only four studies had an age range of <10 years [18,30,34,36]; the largest range was 69 years [36]. One study investigated the relationship between augmented MUCP and age and found a negative correlation [33], similar to other findings on resting MUCP [44][45][46]. Clearly, influence of age on augmented MUCP needs to be evaluated.…”
Section: Experimental Studiesmentioning
confidence: 86%
“…Despite this, only four studies had an age range of <10 years [18,30,34,36]; the largest range was 69 years [36]. One study investigated the relationship between augmented MUCP and age and found a negative correlation [33], similar to other findings on resting MUCP [44][45][46]. Clearly, influence of age on augmented MUCP needs to be evaluated.…”
Section: Experimental Studiesmentioning
confidence: 86%
“…Even if sometimes MUCP is 20 cm of water or less and VLPP is more than 60 cm of water, we can note that studies that have analyzed the risk factor for the failure of continence surgery have only used MUCP of 20 cm water or less as the criterion to define ISD. [23][24][25] Furthermore, ICS did not clearly define ISD, and VLPP cannot be used when patients suffer from a POP of more than grade 1.…”
Section: Discussionmentioning
confidence: 99%
“…The main reason starts in its imprecise clinical definition and work‐up. Known also as type III stress incontinence, patients with ISD have a fixed urethra, absent cervical‐urethral hypermobility on Valsalva, with low MUCP and VLPP Treatment options should increase functional urethral length and include injectable urethral bulking agents, insertion of a pubovaginal sling or intracorporeal external urethral compression devices, such as an AUS…”
Section: Introductionmentioning
confidence: 99%